Characterization of the Circumlimbal Suture Model of Chronic IOP Elevation in Mice and Assessment of Changes in Gene Expression of Stretch Sensitive Channels - Zhao, Da; Nguyen, Christine T. O.; Wong, Vickie H. Y.; Lim, Jeremiah K. H.; He, Zheng; Jobling, Andrew I.; Fletcher, Erica L.; Chinnery, Holly R.; Vingrys, Algis J.; Bui, Bang V. (Frontiers in Neuroscience, 2017)
To consider whether a circumlimbal suture can be used to chronically elevate intraocular pressure (IOP) in mice and to assess its effect on retinal structure, function and gene expression of stretch sensitive channels. Anaesthetized adult C57BL6/J mice had a circumlimbal suture (10/0) applied around the equator of one eye. In treated eyes (n=23) the suture was left in place for 12 weeks whilst in sham control eyes the suture was removed at day two (n=17). Contralateral eyes served as untreated controls. IOP was measured after surgery and once a week thereafter. After 12 weeks, electroretinography (ERG) was performed to assess photoreceptor, bipolar cell and retinal ganglion cell function. Retinal structure was evaluated using optical coherence tomography. Retinae were processed for counts of ganglion cell density or for quantitative RT-PCR to quantify purinergic (P2x7, Adora3, Entpd1) or stretch sensitive channel (Panx1, Trpv4) gene expression. Immediately after suture application, IOP spiked to 33 ± 3 mmHg. After 1 day, IOP had recovered to 27 ± 3 mmHg. Between weeks 2 to 12, IOP remained elevated above baseline (control 12 ± 1 mmHg, ocular hypertensive 18 ± 1 mmHg). Suture removal at day 2 (Sham) restored IOP to baseline level, where it remained through to week 12. ERG analysis showed that 12 weeks of IOP elevation reduced photoreceptor (-18 ± 5%), bipolar cell (-19 ± 6%) and ganglion cell responses (-32 ± 14%) compared to sham controls and respective contralateral eyes (untreated). The retinal nerve fiber layer was thinned in the presence of normal total retinal thickness. Ganglion cell density was reduced across all but the nasal quadrant (superior -12 ± 5%; temporal, -7% ± 2%; inferior -9 ± 4%; nasal -8% ± 5%). Quantitative RT-PCR revealed a significant increase in Entpd1 gene expression (+11 ± 4%), whilst other genes were not significantly altered (P2x7, Adora3, Trpv4, Panx-1). Our results show that circumlimbal ligation produces mild chronic ocular hypertension and retinal dysfunction in mice. Consistent with sustained change to purinergic signaling we found an up-regulation of Entpd1.